2021
DOI: 10.1051/shsconf/202111003006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of podcasting on English learners’ motivation in asynchronous e-learning environment

Abstract: We strongly believe that within the next few years, podcasting is destined to become an important component in the learning environment of the university since educators are trying to integrate the best use of advanced technologies in their courses and remain vigilant to the ever-changing technological landscape. The study aims to validate the idea that podcasts offer teachers a platform to supplement their materials. Despite the potential benefits of podcasts for university education, few researchers have add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Keeping students' motivation to learn is a must then must be motivated by the teachers (Seven, 2020). On the other hand, Marunevich et al, (2021) suggested the motivational factors used podcasts as English learning method are entertainment and convenience as the most prominent factors for using podcasts.…”
Section: Salee: Study Of Applied Linguistics and English Educationmentioning
confidence: 99%
“…Keeping students' motivation to learn is a must then must be motivated by the teachers (Seven, 2020). On the other hand, Marunevich et al, (2021) suggested the motivational factors used podcasts as English learning method are entertainment and convenience as the most prominent factors for using podcasts.…”
Section: Salee: Study Of Applied Linguistics and English Educationmentioning
confidence: 99%
“…In the research study of Marunevich, et al (2021), it was manifested that podcasting serves as authentic material for language instruction, offering educators and learners the opportunity to enhance English language proficiency outside traditional classroom settings. Additionally, it enables flexible access to course materials, empowering individuals to study at their convenience from any location.…”
Section: Related Literature Reviewmentioning
confidence: 99%
“…As a result of the shift to online learning, there has been an uptake in interest in podcasting within diverse higher education contexts (Hitchcock et al, 2021;Marunevich et al, 2021;Donnet and Verpoorten, 2021). Research shows popularity in the use of podcasts among students because of the flexibility of the medium to support their (mobile) learning: podcasts are portable as they can be easily downloaded on personal devices (at a very limited cost as small files) and listened to offline; they can be reviewed and replayed; and they can be listened to while on public transport or walking.…”
Section: Podcasting As a Medium Of Teaching Learning And Assessingmentioning
confidence: 99%